Shop drawing of architectural waterproofing (RFA 032_ Rev B) - WOHA Designs PTE LTD; Web Structures; BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.